Tissue Renin–Angiotensin Systems: A Unifying Hypothesis of Metabolic Disease - Skov, Jeppe; Persson, Frederik; Frøkiær, Jørgen; Christiansen, Jens S. (Frontiers in Endocrinology, 2014)
The actions of angiotensin peptides are diverse and locally acting tissue renin-angiotensin systems (RAS) are present in almost all tissues of the body. An activated RAS strongly correlates to metabolic disease (e.g. diabetes) and its complications and blockers of RAS have been demonstrated to prevent diabetes in humans. Hyperglycemia, obesity, hypertension, and cortisol are well-known risk factors of metabolic disease and all stimulate tissue RAS whereas glucagon-like peptide-1, vitamin D, and aerobic exercise are inhibitors of tissue RAS and to some extent can prevent metabolic disease. Furthermore, an activated tissue RAS deteriorates the same risk factors creating a system with several positive feedback pathways. The primary effector hormone of the RAS, angiotensin II, stimulates reactive oxygen species, induces tissue damage, and can be associated to most diabetic complications. Based on these observations we hypothesize that an activated tissue RAS is the principle cause of metabolic syndrome and type 2 diabetes, and additionally is mediating the majority of the metabolic complications. The involvement of positive feedback pathways may create a self-reinforcing state and explain why metabolic disease initiate and progress. The hypothesis plausibly unify the major predictors of metabolic disease and places tissue RAS regulation in the center of metabolic control.